2007
DOI: 10.1144/sp284.4
|View full text |Cite
|
Sign up to set email alerts
|

Velocity survey of an excavation damaged zone: influence of excavation and reloading

Abstract: During gallery excavation, regardless of the method chosen, the surrounding rock is mechanically disturbed in the case of underground disposal of chemical or radioactive wastes, and such mechanical changes to the rock state can create preferential pathways for the release of material from the waste inside the excavation (e.g. chemical waste gases, brine or dissolved radionuclide) up to the biosphere. The mechanical characterization of this disturbed zone is thus essential in assessing the rock capacity necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Bossart et al (2006) pointed out that there are still a number of open questions related to the evolution of the EDZ, which need to be addressed by conducting careful experiments like those in progress at Mont Terri. One of these experiments has been described by Damaj et al (2007), who showed that the evolution of the EDZ can be surveyed by means of seismic velocity measurements using a multiple array of sensors combined with tomography techniques to image the disturbed zone. Other key experiments needed for progress have been outlined by Bossart (2007), head of the Mont Terri Rock Laboratory project.…”
Section: Repositories In Soft Rock Formationsmentioning
confidence: 99%
“…Bossart et al (2006) pointed out that there are still a number of open questions related to the evolution of the EDZ, which need to be addressed by conducting careful experiments like those in progress at Mont Terri. One of these experiments has been described by Damaj et al (2007), who showed that the evolution of the EDZ can be surveyed by means of seismic velocity measurements using a multiple array of sensors combined with tomography techniques to image the disturbed zone. Other key experiments needed for progress have been outlined by Bossart (2007), head of the Mont Terri Rock Laboratory project.…”
Section: Repositories In Soft Rock Formationsmentioning
confidence: 99%
“…To quantitatively determine the range and variation pattern of EDZs, scholars have conducted studies based on various instruments to record relevant data, such as displacement and strain measurement [19,25], wave velocity testing [24,26], fluid permeation testing [21,27,28], gas permeation testing [5,29], resistivity testing [12,30,31], acoustic emission and microseismic event monitoring [32][33][34], borehole core analysis [13,35], chemical test methods [36,37], seismic wave testing [38][39][40][41], borehole camera technology [42,43], drill hole panoramic digital imaging technology [24], filling resin observation [17,44], and physical model tests [33]. It has been shown that the characteristics of EDZs vary with the rock properties, in situ stress field, geological environment, excavation method, and cavity section geometry, and the results obtained from different research methods vary.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of a damage zone depends on the type of host rock, the geomechanical conditions, and the excavation method ͑Barton, 2006͒. It may be as small as a few centimeters to as large as several shaft/tunnel radii, and its physical properties may vary over time; in argillaceous rocks, the hydraulic conductivities may decrease by orders of magnitude during the first few years after excavation as a result of various self-healing processes ͑Bossart et al., 2004;Blümling et al, 2007͒. In addition to recording microseismic and acoustic emissions ͑Falls and Young, 1998;Young et al, 2000;Young and Collins, 2001;Pettitt et al, 2002͒, various geoelectric ͑Kruschwitz andYaramanci, 2004;Gibert et al, 2006͒ and active ultrasonic ͑ 10 KHz͒ seismic methods ͑Falls and Young, 1998;Young and Collins, 2001;Schuster et al, 2001;Pettitt et al, 2002;Bastiaens et al, 2007;Damaj et al, 2007;Nicollin et al, 2008;Balland et al, 2009͒ have been used to monitor the evolution of EDZs based on data acquired within shafts/tunnels or within boreholes drilled from shafts/tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, microseismicity and active seismic methods provide unique possibilities for remotely monitoring a repository in a largely nonintrusive manner. The principal differences between these methods and those employed from within a repository ͑Falls and Young, 1998;Young and Collins, 2001;Schuster et al, 2001;Pettitt et al, 2002;Bastiaens et al, 2007;Damaj et al, 2007;Nicollin et al, 2008;Balland et al, 2009͒ are the need to record seismic waves that have traveled over longer distances and the associated requirements to employ lower frequency sensors and ͑for the active methods͒ lower frequency more powerful energy sources.…”
Section: Introductionmentioning
confidence: 99%